The dissolution of simulant UK Ca/Zn-modified nuclear waste glass: Insight into Stage III behavior. (2020) - Fisher, Adam J.; Harrison, Mike T.; Hyatt, Neil C.; Hand, Russell J.; Corkhill, Claire L.
ABSTRACT: The dissolution of the United Kingdom's vitrified high-level-waste simulant, CaZn MW28, was investigated following the Product Consistency Test-B protocol for 112 d at 90 ° C and in ultra-high-quality water. Residual rate dissolution (stage II) and rate resumption (stage III), after 28 d, was observed. Thermodynamic modelling suggested that solutions were saturated with respect to Mg- and Zn-bearing phases, and the presence of Mg- and Zn-smectite clays was tentatively observed. The formation of these phases was concurrent with a significant increase in the dissolution rate, similar to Stage III behavior seen in other nuclear waste simulant glass materials, indicating that the addition of Mg and Zn to high-level-waste glass (7.3 wt. % combined) significantly influences the dissolution rate.